Building a better future the Association of Municipal Engineers annual conference 1996, Cheltenham 24 to 27 June 1996 : conference papers. (Thomas Telford, 1996)
Providing access to engineering content from the past, this is the proceedings of the Association of Municipal Engineers' annual conference held in 1996.